Sharing the blame: smoking experimentation and future smoking-attributable mortality due to Joe Camel and Marlboro advertising and promotions. Issue 1 (1st March 1999) - Pierce, John P; Gilpin, Elizabeth A; Choi, Won S
Abstract : BACKGROUND: Despite public denials, internal tobacco company documents indicate that adolescents have long been the target of cigarette advertising and promotional activities. Recent longitudinal evidence suggests that 34% of new experimentation occurs because of advertising and promotions. OBJECTIVE: To apportion responsibility for smoking experimentation and future smoking-attributable mortality among major cigarette brands attractive to young people (Camel and Marlboro). DATA SOURCES, SETTING, AND PARTICIPANTS: Data were from confirmed never-smoking adolescents (12–17 years old) responding to the 1993 (n = 2659) and 1996 (n = 2779) population-based California Tobacco Surveys. MAIN OUTCOMES: Adolescents named the brand of their favourite cigarette advertisements and tobacco promotional items. Using these "market shares" and the relative importance of advertising and promotions in encouraging smoking, we estimated how many new experimenters from 1988 to 1998 in the United States can be attributed to Camel and Marlboro. From other data on the natural history of smoking, we projected how many future deaths in the United States can be attributed to each brand. RESULTS: Although Camel advertisements were favoured more than Marlboro and other brands in 1993 and 1996, the "market share" for promotional items shifted markedly during this period from Camel and other brands towards Marlboro. We estimated that between 1988 and 1998, there will be 7.9 million new experimenters because of tobacco advertising and promotions. This will result in 4.7 million new established smokers: 2.1, 1.2, and 1.4 million due to Camel, Marlboro, and other brands' advertising and promotions, respectively. Of these, 1.2 million will eventually die from smoking-attributable diseases: 520 000 from Camel, 300 000 from Marlboro, and the remainder from other brands. CONCLUSIONS: Our analysis provides a reasonable first estimate at sharing the blame for the long-term health consequences of smoking among the major brands that encourage adolescents to start smoking.